18β-Glycyrrhetinic Acid Delivered Orally Induces Isolated Lymphoid Follicle Maturation at the Intestinal Mucosa and Attenuates Rotavirus Shedding - Hendricks, Jay M.; Hoffman, Carol; Pascual, David W.; Hardy, Michele E. (PLOS ONE, 2012)
Glycyrrhizin, an abundant bioactive component of the medicinal licorice root is rapidly metabolized by gut commensal bacteria into 18β-glycyrrhetinic acid (GRA). Either or both of these compounds have been shown to have antiviral, anti-hepatotoxic, anti-ulcerative, anti-tumor, anti-allergenic and anti-inflammatory activity in vitro or in vivo. In this study, the ability of GRA to modulate immune responses at the small intestinal mucosa when delivered orally was investigated. Analysis of cytokine transcription in duodenal and ileal tissue in response to GRA treatment revealed a pattern of chemokine and chemokine receptor gene expression predictive of B cell recruitment to the gut. Consistent with this finding, GRA induced increases in CD19+ B cells in the lamina propria and B220+ B cell aggregates framed by CD11c+ dendritic cells in structures resembling isolated lymphoid follicles (ILF). Using a mouse model of rotavirus infection, GRA reduced the duration of viral antigen shedding, and endpoint serum antibody titers were higher in GRA-treated animals. Together the data suggest GRA delivered orally augments lymphocyte recruitment to the intestinal mucosa and induces maturation of B cell-rich ILF independently of ectopic antigenic stimulus. These results provide further support a role for dietary ligands in modulation of dynamic intestinal lymphoid tissue.